OPPORTUNITIES RUSSIA GETS IN CASE OF PARTICIPATION IN THE SYSTEM OF THE GLOBAL VALUE CHAINS IN THE ENERGY SPHERE: SOUTH KOREA’S CASE - ALEXANDER VITALEVICH Larionov; KSENIA IGOREVNA Andryushchenko (Мир новой экономики, 2018)
This article aims at analyzing Russia’s potential and opportunities in case of participation in global value chains. After making a theoretical analysis of global value chains functioning authors conclude that Russian state policy should be focused on establishment of the global value chains in the energy sphere. Participation in the global energy chains could also lead to the improving Russian positions in the other value chains. It is also necessary to assess the international experience in this sphere, in particular to consider the case of South Korea, which is the leader in terms of participation in global value chains system. Also it has an experience in the global value chains in the energy sphere. In the end authors concludes that the improving the positions of Russia in terms of global value energy chains could lead to the structural modernization of the economy. That is why it is necessary to use the Russian trade supporting mechanism for increasing Russian positions in Global value chains.